The influence of brand image and promotion on purchase decisions of Eiger footwear products: A case study at the Eiger Grand Depok City branch - Intan, Dewi; Widodo, Djoko Setyo; Rachmawati, Dwi (Jurnal Bisnis Mahasiswa, 2025)
This study aims to analyze the influence of brand image and promotion on purchasing decisions of Eiger shoes (Case Study at Eiger Branch Grand Depok City). The background of this research is based on the relatively low sales figures of Eiger shoe products compared to other Eiger product categories, despite Eiger being recognized as one of the top brands in Indonesia. This research employs a quantitative approach using a survey method. The data analysis technique used is multiple linear regression with the assistance of SPSS software. The results of the study indicate that, partially, brand image does not have a significant influence on purchasing decisions, whereas promotion has a significant effect on purchasing decisions. However, simultaneously, brand image and promotion have a significant influence on purchasing decisions. The coefficient of determination shows that brand image and promotion contribute 55.9% to purchasing decisions. This indicates that an effective promotional strategy can increase consumer purchase interest even if the brand image is not yet fully established. These findings imply that Eiger needs to strengthen its brand image, particularly in terms of product identity and differentiation, while maintaining and optimizing its promotional strategies effectively.